Serine/threonine Kinases Play Important Roles in Regulating Polyunsaturated Fatty Acid Biosynthesis in Synechocystis sp. PCC6803 - Chen, Gao; Cao, Yuelei; Zhong, Huairong; Wang, Xiaodong; Li, Yanle; Cui, Xiaoyan; Lu, Xiaoyuan; Bi, Xiangdong; Dai, Meixue (Frontiers in Bioengineering and Biotechnology, 2021)
Serine/threonine kinases (STKs) play important roles in prokaryotic cellular functions such as growth, differentiation, and secondary metabolism. When the external environment changes, prokaryotes rely on signal transduction systems, including STKs, that quickly sense these changes and alter gene expression to induce the appropriate metabolic changes. In this study, we examined the roles of the STK genes spkD and spkG in fatty acid biosynthesis in the unicellular cyanobacterium Synechocystis sp. PCC6803, using targeted gene knockout. The linoleic acid (C18: 2), γ-linolenic acid (C18: 3n6), α-linolenic acid (C18: 3n3) and stearidonic acid (C18: 4) levels were significantly lower in spkD and spkG gene knockout mutants than in the wild type at a culture temperature of 30℃ and a light intensity of 40 μmol·m−2·s−1. The expression levels of fatty acid desaturases and STK genes differed between the spkD and spkG gene knockout mutants. These observations suggest that spkD and spkG may directly or indirectly affect the fatty acid composition in Synechocystis sp. PCC6803 by regulating the expression of fatty acid desaturases genes. Therefore, the STK genes spkD and spkG play important roles in polyunsaturated fatty acid biosynthesis in Synechocystis sp. PCC6803. These findings could facilitate the development of cyanobacteria germplasm resources that yield high levels of fatty acids. In addition, they provide a theoretical basis for the genetic engineering of cyanobacteria with improved yields of secondary metabolites and increased economic benefits.